KONSEP HARKAT DAN MARTABAT PEREMPUAN DALAM BUKU HABIS GELAP TERBITLAH TERANG KARYA R.A KARTINI DAN RELEVANSINYA TERHADAP PENDIDIKAN ISLAM - Uliyatul Marfu'ah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2020)
The background of this research originated from the admiration of the author of the book Habis Gelap Terbitlah Terang by R.A. Kartini who has an extraordinary spirit in fighting for the dignity of women. Women who are not valued, are not recognized, and do no have the opportunity to develop themselves during the R.A. Kartini, now has freedom. His dignity and recognition are recognized by the community. But along with the development of the era that was so extraordinary. Book Habis Gelap Terbitlah Terang began to be forgotten by the people. This research included qualitative research and the type of research that the authors do is library research. The research approach used is the historical approach. The method of data collection in this study is adjusted to the type of research conducted, namely the research library, then the right data collection method is the collection and documentation method. Data analysis in this study uses content analysis method. Based on the results of research conducted by the author about the concept of the dignity of women in view of R.A. Kartini can be concluded that the concept of the dignity of women in the view of R.A. Kartini has seven concepts: educated women, virtuous women, skilled women, free women who are civilized and educated, men collaborate with women, women who are knowledgeable about religion, and delete the caste system in society. The seven concepts have a close relationship to Islamic education which is focused on the goal of Islamic education, namely facilitates women to develop themselves, both in the realm of individuals, families, social and in work so that we create human being.